Evaluation of stress intensity factors for multiple surface cracks in bi-material tubes - Purbolaksono J.; Ali A.A.; Khinani A.; Rashid A.Z. (2023)
This paper presents stress intensity factors (SIFs) of multiple semi-elliptical surface cracks in bi-material tubes subjected to internal pressure by boundary element method. In this case the water-tube boiler with oxide scale formed on the inner surface due to prolonged exposure at elevated temperature is considered as the bi-material tubes. Variations of modulus of elasticity and thickness for the oxide scale are used to evaluate their effects on the stress intensity factors. The increasing of thickness of the oxide scale causes decreasing values of the normalized stress intensity factor as the modulus of elasticity for the oxide scale is greater than that of the tube metal. Conversely, if the modulus of elasticity for the oxide scale is smaller, the increasing of thickness of the scale would also give increasing values of the normalized stress intensity factor. 2009 Elsevier Ltd. All rights reserved.